The contribution of trees to local livelihoods in urban areas - Kaoma, Humphrey (Rhodes University, Faculty of Science, Department of Environmental Science, 2013)
Trees in natural forests are widely known for their essential contribution to rural livelihoods in developing countries, providing both consumptive and non-consumptive products to rural inhabitants. These benefits are also obtained from trees in urban forests and used by urban households. In the past decades, the role of urban trees to urban livelihoods, municipalities, local and global environment has often been overlooked by researchers and development agencies, and hence are poorly documented, especially in Africa. In South Africa, the increase in urbanisation and urban poverty means many urban residents are expected to be dependent on trees and tree products from homesteads, neighbourhoods and edges of towns. There is however a paucity of literature on the potential of trees in sustaining livelihoods and poverty alleviation in urban areas. This study determined the magnitude and nature of the direct contribution of trees and tree products to local livelihoods in different urban residential areas (informal, Reconstruction and Development Programme (RDP), and township) in three South African towns (Tzaneen, Bela Bela and Zeerust) which cover a rainfall gradient from relatively higher (775 mm p.a.) to low (575 mm p.a.). The results showed that most (90%) households had an interest in planting and managing trees on homesteads, given the high proportion (71%) of residents who had planted trees on their homesteads. The abundance of trees followed the moisture gradient, with Tzaneen having a larger share (46.4%) of trees, followed by Bela Bela (27.5%) and Zeerust (26.1%). Larger plots in the informal residential area accounted for the larger proportion (42.8%) of trees on homesteads, followed by the township (32.9%) and RDP households being the least because they were recently established. Tree density was also higher in the high rainfall town but the pattern did not follow the moisture gradient between Bela Bela and Zeerust due to little rainfall difference. However, tree density across residential areas was similar to the proportion of trees on homesteads in residential areas. The most common tree species were alien, and mainly exotic fruit trees made up two-thirds of the trees encountered. Most households collected various products from urban trees, particularly fuelwood, from edges of towns. This was especially by households with lower cash income. However, fruits were collected from homesteads regardless of the wealth status. Tree products had a significant contribution to the total annual household income, with fuelwood alone contributing up to R5 663 per household per annum, equivalent to two-three month household cash income. Tree products added 20% to total household income, which represents the amount of money households save by collecting tree products for free. Therefore, trees within and around urban areas contribute significantly to livelihoods and reduce poverty in urban areas. There is need therefore to encourage urban residents to plant trees on homesteads and policy makers to come up with policies that promote sustainable harvesting of tree products from areas surrounding urban areas.
Keywords: Trees in cities - -South Africa; Urban ecology (Sociology) -- South Africa; Poverty -- South Africa; Urban forestry -- South Africa; Urban poor -- South Africa; Natural resources -- South Africa; Human-plant relationships -- South Africa